Comparative genomics and prediction of conditionally dispensable sequences in legume–infecting Fusarium oxysporum formae speciales facilitates identification of candidate effectors. (December 2016) - Williams, Angela; Sharma, Mamta; Thatcher, Louise; Azam, Sarwar; Hane, James; Sperschneider, Jana; Kidd, Brendan; Anderson, Jonathan; Ghosh, Raju; Garg, Gagan; Lichtenzveig, Judith; Kistler, H.; et al.
Abstract Background Soil-borne fungi of theFusarium oxysporum species complex cause devastating wilt disease on many crops including legumes that supply human dietary protein needs across many parts of the globe. We present and compare draft genome assemblies for three legume-infectingformae speciales (ff. spp.):F. oxysporum f. sp.ciceris (Foc -38-1) and f. sp.pisi (Fop -37622), significant pathogens of chickpea and pea respectively, the world's second and third most important grain legumes, and lastly f. sp.medicaginis (Fom -5190a) for which we developed a model legume pathosystem utilisingMedicago truncatula . Results Focusing on the identification of pathogenicity gene content, we leveraged the reference genomes ofFusarium pathogensF. oxysporum f. sp.lycopersici (tomato-infecting) andF. solani (pea-infecting) and their well-characterised core and dispensable chromosomes to predict genomic organisation in the newly sequenced legume-infecting isolates. Dispensable chromosomes are not essential for growth and inFusarium species are known to be enriched in host-specificity and pathogenicity-associated genes. Comparative genomics of the publicly availableFusarium species revealed differential patterns of sequence conservation acrossF. oxysporum formae speciales, with legume-pathogenicformae speciales not exhibiting greater sequence conservation between them relative to non-legume-infectingformae speciales, possibly indicating the lack of a common ancestral source for legume pathogenicity. Combining predicted dispensable gene content within planta expression in the model legume-infecting isolate, we identified small conserved regions and candidate effectors, four of which shared greatest similarity to proteins from another legume-infecting ff. spp. Conclusions We demonstrate that distinction of core and potential dispensable genomic regions of novelF. oxysporum genomes is an effective tool to facilitate effector discovery and the identification of gene content possibly linked to host specificity. While the legume-infecting isolates didn't share large genomic regions of pathogenicity-related content, smaller regions and candidate effector proteins were highly conserved, suggesting that they may play specific roles in inducing disease on legume hosts.